2021
DOI: 10.1021/acs.jnatprod.1c00416
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactones from Sigesbeckia glabrescens Possessing Potent Anti-inflammatory Activity by Directly Binding to IKKα/β

Abstract: Chromatographic fractionation of Sigesbeckia glabrescens led to the identification of 10 new sesquiterpene lactones, named siegesbeckialides I−O (1−7) and glabrescones A−C (8−10), along with 14 known analogues. An anti-inflammatory activity assay showed that siegesbeckialide I (1) most potently inhibited LPS-induced NO production in RAW264.7 murine macrophages. Furthermore, siegesbeckialide I suppressed the protein expression of iNOS and COX2, as well as the release of PGE 2 , IL-1β, IL-6, and TNF-α in LPS-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Using a CETSA and DARTS assay, we found that brevilin A not only decreased the thermal stability of IKKα/β, but also inhibited the proteolysis of IKKα/β by the pronase subtilisin. CETSA is an approach to validate the direct bind of small molecule and its target protein by detecting the melt curve of target protein which can shift to a higher or lower temperature when bound by its ligand ( Martinez Molina et al, 2013 ; Gao et al, 2021 ). DARTS is another universally applicable strategy to investigate ligand-target interactions, which takes advantage of a reduction in the protease susceptibility of the target protein upon ligand binding ( Lomenick et al, 2009 ; Yuan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a CETSA and DARTS assay, we found that brevilin A not only decreased the thermal stability of IKKα/β, but also inhibited the proteolysis of IKKα/β by the pronase subtilisin. CETSA is an approach to validate the direct bind of small molecule and its target protein by detecting the melt curve of target protein which can shift to a higher or lower temperature when bound by its ligand ( Martinez Molina et al, 2013 ; Gao et al, 2021 ). DARTS is another universally applicable strategy to investigate ligand-target interactions, which takes advantage of a reduction in the protease susceptibility of the target protein upon ligand binding ( Lomenick et al, 2009 ; Yuan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, LC-MS result demonstrated that brevilin A formed a covalent bond with the thiol of DTT via Michael addition reaction. Although brevilin A possesses another unsaturated C2’=C3’ double bond, the presence of 5′-methyl may decrease the thiol reactivity of this double bond ( Gao et al, 2021 ). Therefore, LC-MS showed an addition of only one molecule of brevilin A to one molecule of DTT via its C2=C3 double bond.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers from China also found that a naturally occurring parthenolide analogue, costunolide ( 2 ), could covalently bind to Cys179 of IKKβ, and inhibit its activity, triggering its protective effect toward atherosclerosis in HFD-fed ApoE -/- mice 124 . Sigesbeckia glabrescens is a species of the genus Sigesbeckia first recorded in Xinxiu Herba written by Su Jing (Tang Dynasty) 125 . Based on its chemical constituents, Gao and colleagues obtained twenty-four sesquiterpenoids, including ten new compounds.…”
Section: Targeting Ikkβ With Pharmacological Small-molecule Compoundsmentioning
confidence: 99%
“…Plants of the genus Siegesbeckia (family Asteraceae) are annual herbs widely distributed in tropical, subtropical, and temperate parts of the world [1,2] . There are three species S. orientalis , S. glabrescens and S. pubescens growing in China and their aerial parts have been used for centuries to treat arthritis, hypertention, malaria, neurasthenia and snakebite [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Plants of the genus Siegesbeckia (family Asteraceae) are annual herbs widely distributed in tropical, subtropical, and temperate parts of the world. [1,2] There are three species S. orientalis, S. glabrescens and S. pubescens growing in China and their aerial parts have been used for centuries to treat arthritis, hypertention, malaria, neurasthenia and snakebite. [3] Phytochemical studies on Siegesbeckia species have been conducted for several decades, and more than 100 compounds have been isolated and characterized, including diterpenoids, [4] sesquiterpenoids, [5] oxylipins, [6] and flavonoids.…”
Section: Introductionmentioning
confidence: 99%